(untitled) (Comprehensive Journal of Science, 2026)
This literature review aims to uncover the psychological and social roots of superstitious thinking among students by analyzing relevant scientific research and studies in different academic environments، A systematic literature review methodology was employed, encompassing experimental, quantitative, and qualitative studies, as well as cross-cultural comparative research published in peer-reviewed journals in both Arabic and English، The review revealed that superstitious thinking is widely prevalent among university and secondary school students, shaped by a combination of psychological factors such as anxiety, lack of personal control, irrational thinking, and psychological trauma, alongside social factors including family upbringing, media influence, and social learning، The prevalence of superstitious thinking varies according to demographic variables such as gender, age, educational level, and religiosity، This paper contributes a comprehensive understanding of the phenomenon and paves the way for further applied and field studies in Arab educational contexts.